Response Option for Attacks Detected by Intrusion Detection System - Shahid, Anwar; Mohamad Fadli, Zolkipli; Aws Naser, Jaber; Jasni, Mohamad Zain; Zakira, Inayat; Odili, Julius Beneoluchi (2015)
In past decades, we have seen that the increasing speed of the network attacks compromising computer system functionality and degrading network performance. The security of these systems has attracted a lot of research in the field of intrusion detection and response system to reduce the effect of these attacks. Response is a major part of intrusion detection system. Intrusion detection system without a timely response is not considered good even they detect threat and generate alarms. Optimum response is based on the selection of proper response option. In this paper, we categorize the attacks and propose some response option to thwart these attacks.